Outcomes of Complete and Early Vitrectomy in Post-Operative Endophthalmitis After Cataract Surgery - Arain, Muhammad Aamir; Muzaffar, Waqar; Farooq, Omer; Azhar, Muhammad Naeem (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the outcomes after complete and early micro-incision vitrectomy surgery in patients with postoperative endophthalmitis after cataract surgery.Study Design: Quasi-experimental study.Place and Duration of Study: Vitreoretina Department, Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Jul 2017 to Dec 2020.Methodology: Thirty (30) patients diagnosed with post-operative endophthalmitis after cataract surgery were included in the study. A vitreous sample was taken and sent for bacterial and fungal culture. A complete vitrectomy was performed after induction of posterior vitreous detachment. The peripheral vitreous base was trimmed, followed by intravitreal antibiotics. Patients were followed up on the first post-operative day and followed up at one week, month and three months. At three months follow-ups, the best corrected visual acuity was noted. Success was defined as best corrected visual acuity (BCVA) of ≥6/60, while failure was defined as BCVA